Restoring trust in organizations and leaders enduring challenges and emerging answers - Kramer, Roderick M. (Roderick Moreland), 1950-; Pittinsky, Todd L. (New York ; Oxford : Oxford University Press, 2012)
This volume adopts the mulidisciplinary approach required to understand the decline in public trust in contemporary institutions, and to propose and assess remedies.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Includes bibliographical references.
Keywords: Organizational behavior; Corporate culture; Trust